Análise da origem da emissão e cinemática do gás na região central da galáxia NGC4546 - Heckler, Kelly Frank (2020)
It is believed that most spheroidal galaxies host a Supermassive Black Hole (SMBH) at their centers and that, at some point, it becomes active, originating an Active Galaxy Nuclei (AGN). The formation and evolution of the galaxy may be directly linked to the growth of SMBH and AGN feedback. In this context, detailed studies on the kinematics and distribution of ionized gas in the central region of the AGN are fundamental to investigate the processes of Feeding and Feedback and their impact on the evolution of galaxies. In this work, we present a detailed analysis of the kinematics of the ionized gas and stars from the inner region at 170 pc of the active galaxy NGC 4546. The main goal of this work is to detect and characterize non-circular motions associated with ionized gas outflows from the AGN. The observations were made with the Gemini Multi-Object Spectrograph (GMOS) in integral field unit (IFU) mode, with a spec- tral coverage of 4736–6806 Å, covering the strongest emission lines observed in AGN spectra. The stellar kinematics was measured by fitting the absorption lines using the penalized Pixel Fitting method (PPXF) using the MILES stellar library as template. The distribution of emis- sion line fluxes and kinematics were measured by fitting the emission-line profiles of the data cube after subtracting the stellar component, using the profit (line-profile fitting) routine. We find that stellar and ionized gas kinematics are dominated by a rotating disk component and that both structures are rotating in opposite directions. The gas kinematics also reveals non-circular motions, interpreted as originating from a biconic outflow produced by the central AGN of NGC 4546. We estimate a value of ∼0.068 MⓈ yr−1 for the ionized gas outflow rate and a kinetic power (E˙cin) of the outflow equivalent to 1.12×1039 erg s−1, which corresponds to only 0.013 % of the AGN bolometric luminosity. Therefore, we find that the E˙cin of the outflow is not high enough to affect the star formation of the galaxy in large scale. This type of AGN Feedback is called as maintenance mode, in which the velocity of the outflows is not high enough to escape the galaxy boundaries, but they can still be efficient in redistributing the gas in its central region.